Evaluate the Quality of Some Imported Composts in Erbil Governorate - Shakar Jamal Aweez; Dalshad Azeez Darwesh; Faris Zaidan Jarjees (Zanco Journal of Pure and Applied Sciences, 2020)
One of the main limitations concerning the use of compost as fertilizer materials is the uncertainty of nutrient availability to plants, especially Nitrogen (N) and Phosphorus (P), due to their presence in both organic and inorganic forms, which are not all immediately plant available. When a good quality compost is applied to an agricultural soil it could reconstitute soils and be an important fertilization backup. The present study was carried out to evaluate the quality of some imported composts in Erbil. The compost samples included 10 most common compost imported from different countries (Bulgari, Pakistan, Russia, Morocco, Egypt, Tabriz, Turkey, Poland, Malaysia, and Jordan) with five replications were bought in different local agrochemical market and shopping. Using a completely randomized design (CRD). The results revealed that the fertilizer index (FI) of imported compost was ranged from 4.42 to 4.92 while the clean index (CI) was ranged from 4.20 to 4.80, all composts have a fertilizer potential value >4. However, the clean index value of compost has medium-heavy metals content, the statistical analysis in the present study indicated that imported composts (Bulgari, Pakistan, Russia, Morocco, Egypt, Poland, Jordan) has a good quality, while (Tabriz, Turkey, Malaysia) are best and proper for agriculture land. In general, the mean concentrations of all heavy metals were lower than the permissible limit of Indian and German standards. However, the concentrations of Cd in Bulgaria, Pakistan, Morocco, Egypt, Tabriz, Poland, Jordan compost were higher than the permissible limit of Indian and Germany standards. In addition, the concentration of Ni in Bulgaria, Morocco, Turkey, Poland and Jordan higher than the Indian and Germany standards (Table 5 and 6).